UJI AKTIVITAS ANTIBAKTERI FRAKSI ETIL ASETAT DAUN JAMBU METE (Anacardium occidentale L.) TERHADAP BAKTERI Bacillus Subtilis dan Pseudomonas aeruginosa - Irawan, Ade; Ulfah, Mariam; Mansor, Khaeron (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2024)
Infectious diseases are caused by various microorganisms including bacteria, viruses, fungi, and parasites. Cashew plants are plants that have antibacterial properties. Saponins, tannins, alkaloids, phenolics and flavonoids have antibacterial properties in cashew leaves. The purpose of this study was to determine the antibacterial activity of the ethyl acetate fraction of cashew leaves against Bacillus subtilis and Pseudomonas aeruginosa bacteria. This research is an experimental study. Ethyl acetate fraction was obtained by liquid-liquid fractionation method. Antibacterial test used concentrations of 10%, 20% and 30%, positive control Ciprofloxacin, negative control DMSO 10% with paper disc diffusion method. The results of phytochemical screening of ethyl acetate fraction of cashew leaves were positive for flavonoids, saponins and tannins. The average diameter results of the antibacterial test of Bacillus subtilis concentrations of 30% (4.5 mm), 20% (3.5 mm) and 10% (2.5 mm), while Pseudomonas aeruginosa concentrations of 30% (5 mm), 20% (3.8 mm) and 10% (1.6 mm). The ethyl acetate fraction of cashew leaves showed antibacterial activity against Bacillus subtilis and Pseudomonas aeruginosa bacteria.